2011
DOI: 10.1371/journal.pone.0025935
|View full text |Cite
|
Sign up to set email alerts
|

Heme-Induced ROS in Trypanosoma Cruzi Activates CaMKII-Like That Triggers Epimastigote Proliferation. One Helpful Effect of ROS

Abstract: Heme is a ubiquitous molecule that has a number of physiological roles. The toxic effects of this molecule have been demonstrated in various models, based on both its pro-oxidant nature and through a detergent mechanism. It is estimated that about 10 mM of heme is released during blood digestion in the blood-sucking bug's midgut. The parasite Trypanosoma cruzi, the agent of Chagas' disease, proliferates in the midgut of the insect vector; however, heme metabolism in trypanosomatids remains to be elucidated. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 59 publications
5
49
0
Order By: Relevance
“…In summary, we demonstrated that modifying the expression levels of an element from the 8-oxoG repair system can influence the parasite cell viability in both replicative phases, as previously observed for the parasite antioxidant machinery [62]. Considering that oxidative stress is important to T. cruzi proliferation in both replicative forms as demonstrated by Paiva et al [54] and Nogueira et al [53], mechanism for counteracting DNA oxidative damage would be of great importance for this parasite. T. cruzi DNA repair machinery presents some particular features from typical eukaryotic DNA repair machinery.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In summary, we demonstrated that modifying the expression levels of an element from the 8-oxoG repair system can influence the parasite cell viability in both replicative phases, as previously observed for the parasite antioxidant machinery [62]. Considering that oxidative stress is important to T. cruzi proliferation in both replicative forms as demonstrated by Paiva et al [54] and Nogueira et al [53], mechanism for counteracting DNA oxidative damage would be of great importance for this parasite. T. cruzi DNA repair machinery presents some particular features from typical eukaryotic DNA repair machinery.…”
Section: Discussionsupporting
confidence: 79%
“…The recent findings of Nogueira et al [53] confirm that low levels of ROS production induced by heme in T. cruzi epimastigotes favors parasite proliferation via a Ca 2+ calmodulin kinase II (CaMKII)-like pathway. In addition, antioxidant activity (urate and GSH) inhibited heme-induced ROS and parasite proliferation [53]. In addition, Paiva et al [54] demonstrated that maintenance of high parasite burden during T. cruzi infection might be dependent of oxidative stress generation.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, the consequences to redox homeostasis revealed to be more complex than previously anticipated. While insect vectors reduce mitochondrial oxidant production in different species and tissues (Gonçalves et al, ; Oliveira et al, ; Bottino‐Rojas et al, ; Gandara et al, ), blood dwelling parasites boost mitochondrial ROS generation when exposed to blood products (Gonçalves et al, ; Nogueira et al, ; Oliveira et al, ; Nogueira et al, ). Despite important biological aspects underlying the management of a blood meal, including diuresis, host hormone signaling, and nutritional overload were previously reviewed (Luckhart and Riehle, ; Orchard, ; Sterkel et al, ), here, we will discuss how blood derived products modulates energy metabolism in hematophagous organisms of medical importance, focusing on the observed changes in mitochondrial function and structure.…”
Section: A Switch In Energy Metabolism As a Biochemical Hallmark In Bmentioning
confidence: 99%
“…Heme-induced proliferation of T. cruzi culture forms is mediated by activation of a CaMKII and prevented by inhibitors of this enzyme (KN-93, Myr-AIP) [74]. Activation of this CaMKII is mediated by the enhanced reactive oxygen species (ROS) formation by heme [75,76]. …”
Section: Ca2+ Signaling In Trypanosomatidsmentioning
confidence: 99%